Afroditi Papadogeorgopulu (1972). «Hèmon va fotre el camp» - Almirall, Jaume (ΑΕΡΗΔΕΣ / TORRE DELS VENTS, 2024)
Αφροδίτη Παπαδογεωργοπούλου. 2024. «Ο Αίμωνας το έσκασε» [«Hèmon va fotre el camp»]. Khartis [Mapa] 67.